The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1136/adc.60.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex infections in atopic eczema.

Abstract: SUMMARY One hundred and seventy nine children with atopic eczema were studied prospectively for two and three quarter years; the mean period of observation being 18 months. Ten children had initial infections with herpes simplex. Four children, very ill with a persistently high fever despite intravenous antibiotics and rectal aspirin, continued to produce vesicles and were given intravenous acyclovir. There were 11 recurrences among five patients. In two patients the recurrences were as severe as the initial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 14 publications
3
38
1
Order By: Relevance
“…Intermittent long-term treatment of infants with pimecrolimus for up to 2 years did not alter the frequency of skin infections over time, as the incidence of skin infections was comparable in the first and second years of treatment. Compared with control treatments [36, 37], the incidence of all bacterial and viral infections with pimecrolimus in infants treated for more than 1 year was low [31]. With regard to the specific types of infection, a meta-analysis of paediatric patients has demonstrated that the incidence of bacterial skin infections was slightly lower in the pimecrolimus group, compared with the vehicle group (table 2) (unpublished data).…”
Section: Skin Infectionsmentioning
confidence: 99%
“…Intermittent long-term treatment of infants with pimecrolimus for up to 2 years did not alter the frequency of skin infections over time, as the incidence of skin infections was comparable in the first and second years of treatment. Compared with control treatments [36, 37], the incidence of all bacterial and viral infections with pimecrolimus in infants treated for more than 1 year was low [31]. With regard to the specific types of infection, a meta-analysis of paediatric patients has demonstrated that the incidence of bacterial skin infections was slightly lower in the pimecrolimus group, compared with the vehicle group (table 2) (unpublished data).…”
Section: Skin Infectionsmentioning
confidence: 99%
“…Eczema herpeticum is a form of herpes simplex virus infection with extensive skin involvement, occurring predominantly among patients with AD. 47,49 The actual incidence of eczema herpeticum among infants with AD is unknown. In total, 10 infants treated with 1% pimecrolimus cream in the 6 clinical studies experienced clinically diagnosed eczema herpeticum.…”
Section: Most Frequently Reported Adverse Eventsmentioning
confidence: 99%
“…It has been reported that patients with AD are at higher risk of herpes simplex infections, compared with the general population. [47][48][49] The ID rate of herpes simplex virus skin episodes, including eczema herpeticum and severe initial infections, among children with AD has been estimated to be 4.7 cases per 1000 patient-months of follow-up monitoring (95% CI: 2.6 -7.7) (unpublished report on file at Novartis Pharma AG). The ID rates of herpes simplex virus infections, not including eczema herpeticum, observed during the DB phases of the studies were 0.8 cases per 1000 patient-months in the pimecrolimus group and 1.7 cases per 1000 patientmonths in the vehicle group (relative risk: 0.462; 95% CI: 0.04 -9.93; P ϭ .528).…”
Section: Most Frequently Reported Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other specific types of skin infections reported in patients treated with pimecrolimus cream 1% in clinical trials, such as impetigo, folliculitis, furuncle, skin papillomas (viral warts) and mollusca contagiosa (tables 3 and 4) are infections known to occur more frequently in patients with AD than in normal individuals [47,48,49,50]. None of these infections occurred significantly more frequently in patients treated with pimecrolimus cream 1% than in patients who received the vehicle (tables 3 and 4).…”
Section: Adverse Events In Clinical Trialsmentioning
confidence: 99%